Understanding basic mechanics : workbook - Reif, F. (Frederick), 1927- (New York : John Wiley and Sons, 1995)
This book is divided into three parts: Description of particle motions; Motion and interaction of particles; and Motion and interaction of systems.
Keywords: Mechanics; Applied; Mechanics, Applied